Positive regulation of oxidative phosphorylation by nuclear myosin 1 protects cells from metabolic reprogramming and tumorigenesis in mice - Venit, Tomas; Sapkota, Oscar; Abdrabou, Wael Said; Loganathan, Palanikumar; Pasricha, Renu; Mahmood, Syed Raza; El Said, Nadine Hosny; Sherif, Shimaa; Thomas, Sneha; Abdelrazig, Salah; Amin, Shady; Bedognetti, Davide; et al. (Nature communications, 2023)
Metabolic reprogramming is one of the hallmarks of tumorigenesis. Here, we show that nuclear myosin 1 (NM1) serves as a key regulator of cellular metabolism. NM1 directly affects mitochondrial oxidative phosphorylation (OXPHOS) by regulating mitochondrial transcription factors TFAM and PGC1α, and its deletion leads to underdeveloped mitochondria inner cristae and mitochondrial redistribution within the cell. These changes are associated with reduced OXPHOS gene expression, decreased mitochondrial DNA copy number, and deregulated mitochondrial dynamics, which lead to metabolic reprogramming of NM1 KO cells from OXPHOS to aerobic glycolysis.This, in turn, is associated with a metabolomic profile typical for cancer cells, namely increased amino acid-, fatty acid-, and sugar metabolism, and increased glucose uptake, lactate production, and intracellular acidity. NM1 KO cells form solid tumors in a mouse model, suggesting that the metabolic switch towards aerobic glycolysis provides a sufficient carcinogenic signal. We suggest that NM1 plays a role as a tumor suppressor and that NM1 depletion may contribute to the Warburg effect at the onset of tumorigenesis. Metabolic reprogramming is a hallmark of tumorigenesis. Here, the authors show that nuclear myosin 1 regulates mitochondrial oxidative phosphorylation via the TFAM and PGC1α transcription factors and suggest its depletion contributes to the Warburg effect during tumorigenesis.